CORONAVIRUS VARIANTS-ASSOCIATED-PSYCHOLOGICAL DISTRESS IN ARAB COMMUNITIES - Shahin, Mahmoud (Universitas Islam Negeri Alauddin Makassar, 2022)
The confusion surrounding the coronavirus disease (COVID-19) pandemic and its variants, such as Delta and Omicron, has created negative health and psychological consequences globally. The study aimed to compare the psychological influence of the COVID-19 variants on the general population of two Arab countries after some time of the pandemic. A descriptive, comparative, cross-sectional study was carried out in January 2022 on 1,219 participants from the Kingdom of Saudi Arabia (KSA) and Egypt. The COVID-19 anxiety scale (CAS), depressive symptoms questionnaire (DSQ), and obsessive-compulsive disorder (OCD) questionnaire were used to assess the psychosocial status of the participants. The results revealed a statistically significant difference in all psychological distress parameters between Egyptian and Saudi participants with Egyptians more likely to suffer psychological problems. Egyptians had more psychological distress than Saudis during the pandemic of the COVID-19 variants. The findings also revealed that the anxiety, depression, and OCD scores had a significantly positive correlation with each other. In conclusion, the study indicated a difference in the psychological state of the population and showed different reactions to this epidemic and varying levels of responses to the Corona pandemic and its variants. It is recommended to use psychological counseling and psychoeducation via social media taking into consideration the psychosocial and financial factors of the population to avoid poor follow-up and provide insight into the impact of a health emergency on the public’s psychological well-being over an extended period. Keywords: Anxiety, COVID-19 variants, depression, obsession, and psychological distress.